Programa mnémico cognitivo para mejorar los procesos de la memoria de los alumnos del primer año de las escuelas académico profesionales de educación inicial de las facultades de educación de la unt, upao y ucv - Pollio Rojas, Mariela Herlinda (2008)
The problem of this research work was, To what extent a mnemonic cognitive program improves the processes of memory of the first year students of the Academic Professionals Schools of Nursery Education of the Faculties of Education of the UNT, UPAO and UCV? The theoretical grounds for the mnemonic cognitive program, were based on Ausubel, Gagné and Piaget theories about memory. The work of these authors was also used to elaborate the questionnaire about the use of mnemonic strategies. The sample consisted of 144 students. The questionnaire measured the use of mnemonic strategies to codify, store and recover information by the students, before (pre test) and after (post test) the application of the program. It was found that: 1) the applied pre test revealed a low percentage of use of mnemonic strategies to codify, store and recover information by the students of the UNT, UPAO and UCV and, 2) the applied post test revealed a high percentage of use of mnemonic strategies to codify, store and recover information by the students of the UNT and a low percentage by the students of UPAO and UCV. In summary, the mnemonic cognitive program improved meaningfully the processes of the memory of the first year students of the Academic Professionals Schools of Nursery Education of the Faculties of Education of the UNT, UPAO and UCV.